1977
DOI: 10.1139/f77-086
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Diatom Frustules and Recycling of Amorphous Silicon in Lake Michigan

Abstract: We measured the concentration of diatom frustules and amorphous silicon per gram of dry sediment at 5-m intervals in the upper water column (0–40 m), in sediment traps placed at 37 and 60 m below the surface, and in a sediment core. The average concentration of frustules per gram of dry suspended sediment in the water column was 3.14 × 108. The 37 and 60 m trap sample averages were 1.16 × 108 and 5.03 × 107 frustules/g dry sediment, respectively. Subsamples from the sediment core averaged 6.31 × 106 frustules/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…The concentrations of DSi in the interstitial water of the top part of the sediment profile in Lake Kuutsjärvi (21-24 mg l -1 , Fig. 4) were high compared to these values and to other values measured from the uppermost layers of lake sediment profiles (Harriss 1967;Bailey-Watts 1976;Nriagu 1978;Cornwell and Banahan 1992;Parker et al 1977;Peinerud 2000), where values above 20 mg l -1 were mostly found only at 10-20 cm sediment depth. As supersaturation of the sediment interstitial water with DSi is a factor retarding further dissolution (cf.…”
Section: Autochthonous Diatom Production?mentioning
confidence: 58%
“…The concentrations of DSi in the interstitial water of the top part of the sediment profile in Lake Kuutsjärvi (21-24 mg l -1 , Fig. 4) were high compared to these values and to other values measured from the uppermost layers of lake sediment profiles (Harriss 1967;Bailey-Watts 1976;Nriagu 1978;Cornwell and Banahan 1992;Parker et al 1977;Peinerud 2000), where values above 20 mg l -1 were mostly found only at 10-20 cm sediment depth. As supersaturation of the sediment interstitial water with DSi is a factor retarding further dissolution (cf.…”
Section: Autochthonous Diatom Production?mentioning
confidence: 58%
“…Apparently a large fraction of the material sedimented during April-June was inorganic materials that are suspended during winter circulation and thermally mixed periods in spring. Parker et al (1977) found that the fraction of biogenic silica in monthly sediment trap samples decreased from 3 1% in May to 6% in October, and then increased slightly in November.…”
Section: Discussionmentioning
confidence: 94%
“…Fee (1973) found that primary production rates were about twice as large in the nearshore as the average of 130 g C~rn-~*yr-' in offshore waters. Parker et al (1977) estimated annual primary production of 100 g C*m-2* yr-' at ANL 5, which is representative of Fee's offshore rate, and an annual silica requirement for offshore diatom production of 114 g Si02*m-2.yr-1. We calculated a biogenic silica flux at ANL 5 of 110 g Si02.…”
Section: Discussionmentioning
confidence: 99%
“…As the diatoms died and were removed from the water column or surface sediments, the silica was recycled, leading to few remains in the sediment. Extensive dissolution and silica recycling has been observed in more productive temperate systems (e.g., Parker et al 1977aParker et al , 1977bNriagu 1978;Conley et al 1988;Ryves et al 2013) and in Alaska (Cornwall and Banahan 1992). The increased terrestrial vegetation production, along with the continual presence of permafrost, may have reduced input of silica to the lake.…”
Section: Diatom-free Zones In Arctic Lake Sedimentsmentioning
confidence: 99%